The morning after : sexual politics at the end of the Cold War - Enloe, Cynthia H., 1938- (University of California Press, 1993)
Looking at the end of the Cold War - in the United States, Russia, Bosnia, El Salvador, and Vietnam, among other countries - Cynthia Enloe places women at the center of international politics. From the Tailhook scandal to the fall of the Berlin Wall to the NAFTA agreement, Enloe makes incisive connections - between demilitarization and ideologies about motherhood and the family, between lesbians and national security, between the events "out there" and women's behavior "back here." Focusing on the inextricable, sometimes subterranean, relationship between the politics of sexuality and the politics of militarism, Enloe links jobs, domestic life, military networks, and international relations. From the Salvadoran revolutionary who removes her IUD to begin a new life as a wife and mother to the Estonion woman who faces down a fully armed Russian soldier, Enloe charts new definitions of gender roles, sexuality, and militarism at the end of the twentieth century. Emerging nationalist movements, while often viewed as liberatory, serve ironically to reestablish the privileges of masculinity and grease the wheels of a new militarism. From the new states of Eastern Europe to Kuwait to Latin America, Enloe not only documents ongoing assaults upon women but also suggests what they tell us about living in this post-Cold War era. The rape of Bosnian women and the prostitution around American military facilities are just two of the graphic reminders of women's continuing disenfranchisement. Other forms are more subtle. Yet in this gray dawn of the "morning after," rife with the contradictions and tensions of a new era, the politics of sexuality has already shifted irrevocably. Femininity and masculinity are being contested and refashioned as women - soldiers, mothers, legislators, and workers - glimpse the exciting possibilities of democratization while confronting the realities of a turbulent, largely patriarchal world. Deciphering the sexual tea-leaves of this tumultuous new era, The Morning After is an eye-opener for everyone who cares about contemporary sexual politics
Keywords: Sex role.; Man-woman relationships.; Feminist theory.; Cold War.; Post-communism.; Feminist theory; Gender Role; Rôle selon le sexe.; Relations entre hommes et femmes.; Théorie féministe.; Guerre froide.; Postcommunisme.; sex role.; SOCIAL SCIENCE -- Gender Studies.; Man-woman relationships; Post-communism; Sex role; Koude Oorlog.; Vrouwen.; Internationale politiek.